CONGESTION AS A RESULT OF SCHOOL AND SHOPPING CENTER ACTIVITY - Meike Kumaat; Agus Taufik Mulyono; Ade Sjafruddin; Bagus Hario Setiadji (Chemical Engineering Diponegoro University, 2015)
Development of land use in public facilities such as shopping center and school gives an impact on transportation problem in Manado City, North Sulawesi. To determine factors which have causal relationship with congestion as a result of school and shopping center activity then it need to be assessed and studied. Descriptive study with observational survey was used in this study. The study ran Structural Equation Modelling (SEM) by using AMOS program. Estimated method was used to calculate sample size then found 300 repondents, comprised : visitors and mall managers, school visitors, parents, school managers, Public Works department, and urban planning department .The study yielded a statistically significant correlation between school and shopping center activity with congestion s. The result indicated that school activity was positively related to congestion with p value at p=0,000 (p ≤ 0,05). Shopping center activity was positively related to congestion with p value at p=0,000 (p ≤ 0,05). The closer proximity from school to shooping center will causes severe traffic congestion. The relationship between school facility with proximity was found in p value at p=0,000 (p ≤ 0,05) . The relationship between shopping center facility with proximity was found in p value at p= 0,020 (p ≤ 0,05). While, the relationship between proximity with congestion was p= 0,008 (p ≤ 0,05). Monastery school and Mega Mall activity were affecting congestion because a closer proximity of two facilities. This indicates that the occurence of traffic congestion in Monastery School may be dependent on existence of Piere Tendean road link